ANALISIS FAKTOR-FAKTOR PENGHAMBAT KEMAMPUAN MEMBACA SISWA - Salsabil, Syafira Nurmala; Ferianto, Ferianto (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Learning in Elementary School (SD), especially in reading ability is a basic thing that must be owned by every child. If a child at lower school age does not quickly acquire reading skills, then he or she will face many difficulties in pursuing various fields of research in later classes. This study aims to describe what are the factors that hinder reading ability in Class 2 at SDN Dawuan Tengah 1. This method uses qualitative evaluation research to describe and analyze phenomena that occur in SDN Dawuan Tengah I in terms of reading ability. The data collection techniques used are observation and interviews. The subject of this study was class 2A of SD Negeri Dawuan Tengah 1 with a total of 28 students consisting of 13 male students and 15 female students. The analysis technique used is data reduction, data presentation and drawing conclusions. The results of the study showed that the factors inhibiting reading ability in Grade 2 at SDN Dawuan Tengah 1 were intellectual factors, environmental factors, motivation, and interests.